Deep Inferior Epigastric Flap Combined Bilateral-Anterolateral Thigh Flap for the Coverage of Both Lower Extremity Soft-Tissue Defect: A Case Report and a Literature Review - Liu X; Huo D; Wu G (Dove Medical Press, 2021)
Xilin Liu,* Da Huo,* Guangzhi Wu Department of Hand Surgery, China-Japan Union Hospital of Jilin University, Changchun, 130033, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guangzhi Wu Tel +86-13944181019Email wuguangzhi@jlu.edu.cnBackground/Purpose: Anterolateral thigh perforator (ALTP) flap and deep inferior epigastric perforator (DIEP) flap have been advantageous over traditional myocutaneous flaps as they preserve the integrity of donor site muscles and minimize the damage and complication to donor site structures. Here, we reported the efficacy of free ALTP and DIEP in the repair of large skin area and soft tissue defects on both lower limbs after trauma.Case Report: A 19-year-old female traffic accident victim presented with multiple open bilateral fractures to the lower extremities with joint dislocation, massive skin and soft tissue defects, and multiple soft tissue contusion. Wounds on both lower extremities were covered with VSD (Vacuum Sealing Drainage). The tibiofibular and ankle joints on both lower limbs were fixed using external fixators. DIEP and ALTP flap were performed at different times.Results: After transfer, the vascular pedicle was anastomosed to the anterior tibial artery, posterior tibial artery, and the accompanying vein. After the operation, the donor site was directly closed and sutured. All flaps survived with a good appearance, leaving only a linear scar at the donor site.Conclusion: This case shows that free ALTP and DIEP flaps are ideal for repairing large skin area and soft tissue defects in bilateral lower limbs after trauma.Keywords: anterolateral thigh perforator flap, deep inferior epigastric perforator flap, soft tissue repair, skin repair